?PRODUCTION OF HAPLOID PLANTS IN CROSSES BETWEEN F1-GENERATION OF WHEAT WITH MAIZE (Biological Sciences - PJSIR, 2000)
Eight crosses in F,-generation of bread wheat were crossed with maize variety C-17. Fertilization frequency ranged from 10-21.9%ofpollinatedflorets.Atotalof50embryoswererecoveredfrom492floretsand IS embryosgerminated to havehaploidseedlings.